MEDICAL SUPPORT IN EARTHQUAKE DISASTER – 2005: Medical Support - Seir, Farrukh; Sukhera, Mumtaz (Pakistan Armed Forces Medical Journal, 2006)
IntroductionThe military serves to defend and protect the nation, but in extensive natural disasters the military is invariably the first responder owing to its befitting field training and infrastructure. At about 08:43 AM on 8th Oct 2005, a massive Earth Quake measuring 7.6 on the Richter scale hit the Azad Jammu and Kashmir and northern parts of North West Frontier province causing colossal loss of life and property. The immediate impact of the earthquake was so severe, that it badly damaged the existing infrastructure especially roads/ communication and public services including health sector, to an extent which was beyond comprehension. The initial damage remained obscure due to communication disruption and once the enormity of devastation unfolded, government and in particular the army and other NGOs/ Volunteer Groups responded to the situation and started the relief operations. The earthquake was followed by forceful hailstorm and torrent rains in most of quake hit areas; adding up to the plight of effected populace which was seeking refuge in open.The people of Pakistan, rose as one, their response was indeed overwhelming and heart warming for any country. They galvanized, they jelled into one and reached out from the length and breadth of the country for their brethren in distress in the affected areas of Azad Kashmir and NWFP. The army moved fast, the first and foremost priority in medical assistance of the army was in the form of evacuation of the casualties which came up as a mammoth task, challenging the preparedness and effectiveness of national medical resources. In that hour of panic and chaos, the Army Medical Corps took up the challenge with considerable courage and responded to the call of duty. By 5 O’clock in the evening of 8th October, there were helicopters hovering over every hospital in Islamabad and Rawalpindi waiting to land and unload the casualties. On the same evening the engineers of Pakistan army were moved to open the road access to Muzaffarabad and by about 12’O clock the next day, one of the road accesses via Abbottabad and Garhi Habibullah to Muzaffarabad was opened. This was the greatest achievement which led to faster supplies to the forward areas. By the morning on next day, army strength of about 3000 people had reached their locations and within three to four days forty-fifty thousand troops in the form of two divisions reached their locations. This is no mean achievement by any army of the world.The international community, the United Nations, the NGOs all moved fast as well. Without their help we would have lost many lives. Pakistan lacked the technical expertise of reaching out the casualties and saving people trapped under the rubble. It was these rescue teams that helped us. Tremendous support was available to the relief operation by the international community, by the people of Pakistan within Pakistan and by the expatriate Pakistanis. The international community, the Pakistan NGOs and the foreign NGOs, the UNO – all played an exceptional role in making the relief operation a success